Effects of Probiotic Supplements on Adolescent Mental Health - Rony Setianto; Selvana Stien Tulandi; Rini Ambarwati; Halimatussakdiah Halimatussakdiah; Muntasir Muntasir (Journal of World Future Medicine, Health and Nursing, 2024)
Adolescent mental health is an important issue that needs serious attention, considering its impact on the quality of life in the future. Recently, attention to the relationship between mental health and gut bacteria (gut microbiota) has increased. Probiotic supplements have been identified as one possible way to improve adolescent mental health through their influence on the gut microbiota. This study aimed to explore the effects of probiotic supplements on adolescent mental health, focusing on symptoms of anxiety, depression and stress. The research was conducted using a randomized controlled experimental design, with adolescent participants aged between 13-18 years. Participants were divided into two groups, where one group received probiotic supplements during the study period, while the control group received a placebo. Internationally recognized scales were used to measure symptoms of anxiety, depression, and stress before and after the intervention. The results showed that adolescents who received probiotic supplements experienced a significant reduction in symptoms of anxiety and depression compared to the control group. In addition, stress levels also showed a significant reduction in the group receiving probiotic supplements. The implementation of this study provides promising initial evidence of the positive effects of probiotic supplementation on adolescent mental health. With this research, the application of probiotic supplements as a mental health intervention in adolescents becomes an attractive alternative. However, further research is needed to understand the mechanisms underlying the relationship between probiotic supplements and adolescent mental health and to determine the most effective dosages and formulations.